Child protective services decision-making: The role of children's race and county factors - Maguire-Jack, Kathryn; Font, Sarah A; Dillard, Rebecca (American journal of orthopsychiatry, 2020)
The current study investigates the role of race and county characteristics in substantiation and out-of-home placement decisions in the United States. Using multilevel models, we analyzed data from counties in the United States available through the National Child Abuse and Neglect Data Systems and Adoption and Foster Care Analysis and Reporting System to investigate the interactions between children's race and the context in which they live. Our sample consisted exclusively of children whose cases had been investigated; therefore, we were able to focus on the role played by race and county characteristics in substantiation and out-of-home placement decisions made by Child Protective Services, net of the heightened risk factors (or potential biases) that lead to disparate rates of reporting. Adjusting for state and county of investigation, Black, American Indian/Alaskan Native, and multiracial children were more likely than White (non-Hispanic) children to be substantiated or placed out of home, whereas Asian children were less likely to be substantiated or placed out of home. Notably, differences across groups are far smaller in magnitude when demographic and geographic differences are taken into account. Higher county-level poverty, percentages of Black residents, and juvenile arrest rates were associated with lower odds of substantiation and out-of-home placement among investigated children, whereas an elevated percentage of single-headed households was associated with higher odds of both outcomes. We also found that living in a rural county was associated with greater odds of substantiation but lower odds of out-of-home placement. Important differences by race were found for these associations. (PsycINFO Database Record (c) 2020 APA, all rights reserved).